Empowering micro-enterprises by improving human resource skills through food entrepreneurship in Tuban District - Ilma Afit Ardiana; Isa Anshori (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines the empowerment of micro-enterprises through human resource (HR) skills development programmes in Tuban Regency, with a particular focus on food entrepreneurship initiatives implemented by the local government. Grounded in Theodore W. Schultz’s Human Capital Theory, the research analyses the effectiveness of training programmes in strengthening the capacity and competitiveness of micro-entrepreneurs. Employing a descriptive qualitative approach, data were collected through in-depth interviews, field observations, and documentation involving micro-business actors, MSME facilitators, and local government officials. The findings reveal that training programmes related to local product processing, business legality, and digital marketing have contributed positively to improving entrepreneurial competencies, business knowledge, and operational capabilities among micro-enterprise actors. These initiatives have enhanced participants’ readiness to compete within increasingly dynamic market environments and encouraged greater business sustainability. Nevertheless, the study also identifies several challenges, particularly regarding the need for stronger post-training assistance, mentoring, and more equitable access to empowerment programmes to ensure broader and more sustainable impacts. The study contributes to the literature on micro-enterprise development, human capital enhancement, and local economic empowerment by providing empirical insights into community-based entrepreneurship development in regional Indonesia. Keywords: Human Resource Training; MSME Empowerment; Micro Enterprises